(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2011)
The simple method of comparison of light-emitting diodes after a light stream and possible construction of setting of this method are presented in this article. Parabolic mirrors are specially entered in a construction, as directing concentrators of light stream, and vibromotor with automatic control. Near one focus of mirrors set a light-emitting diode which is envisaged on a vibromotor, and on an opposite mirror in focus fasten fotodetector. After including to the vibromotor, by oscillation vibrations a light-emitting diode in one of moments is combined with focus of parabolic mirror. Whereupon, a light stream is directed by a parabolic mirror on opposite and gathers in focus last, where and registered by fotodetector. The entered vibration imitates the frequent measuring of stream that saves time on realization of measuring.